Value of laparoscopy in the study of intrabdominal diffusion .of malignant tumors - Piñeyro, Alberto; Perrier, José P; Piñeyro, Luis (Cirugía del Uruguay, 1981)
The authors consider laparoscopy -particularly with the technical advances introduced during the last few A. Prn"EYRO Y COL. years- as an extremely useful procedure in the study of intrabdominar diffusion of malignant tumors. It is particularly reliable in detection of liver metastases.